2012
DOI: 10.1007/978-3-642-28537-0_11
|View full text |Cite
|
Sign up to set email alerts
|

Detecting Pedophile Activity in BitTorrent Networks

Abstract: Abstract. The wide spread of Peer-to-Peer networks makes multimedia files available to users all around the world. However, Peer-to-Peer networks are often used to spread illegal material, while keeping the source of the data and the acquiring users anonymous. In this paper we analyze activity measurements in the BitTorrent network and examine child sex abuse activity through the Mininova web portal. We detect and characterize pedophilic material in the network, and also analyze different aspects of the abuser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 5 publications
0
9
0
Order By: Relevance
“…Piracy websites are known to provide links to CEM [8]. In a longitudinal study, Prichard et al [9] found that the term "pthc" (pre-teen hardcore) was consistently more frequently searched for than Harry Potter movies on what was the then #2 most popular torrent site. Other studies have consistently linked piracy sites and CEM [9].…”
Section: Links To Child Exploitation Materialsmentioning
confidence: 99%
See 3 more Smart Citations
“…Piracy websites are known to provide links to CEM [8]. In a longitudinal study, Prichard et al [9] found that the term "pthc" (pre-teen hardcore) was consistently more frequently searched for than Harry Potter movies on what was the then #2 most popular torrent site. Other studies have consistently linked piracy sites and CEM [9].…”
Section: Links To Child Exploitation Materialsmentioning
confidence: 99%
“…This category or genre of manga is known to depict simulated sexual acts between adults and children, between children or between children and animals. In many countries, such as the United States and the United Kingdom, obscenity laws cover the depiction of child sexual abuse in cartoon format; in a highly-publicised case, Christopher Handley, an American citizen, pleaded guilty to possessing manga books depicting child sex abuse, even though he possessed no other types of CEM 9 . He received a sentence of 6 months.…”
Section: Links To Child Exploitation Materialsmentioning
confidence: 99%
See 2 more Smart Citations
“…It leads to the collection of very large scale datasets and the design of a semantic filter, the performances of which were assessed by world-wide experts in the domain [LMF12]. These authors have then realized experiments to obtain reliable estimates of the fraction of pedophile queries, which were completed by another team on different networks [RSVZ12].…”
Section: Introductionmentioning
confidence: 99%